From a helix to a small cycle: metadynamics-inspired alpha v beta 6 integrin selective ligands - Di Leva, Francesco Saverio; Tomassi, Stefano; Di Maro, Salvatore; Reichart, Florian; Notni, Johannes; Dangi, Abha; Marelli, Udaya Kiran; Brancaccio, Diego; Merlino, Francesco; Wester, Hans-Juergen; Novellino, Ettore; Kessler, Horst; et al. (Angewandte Chemie-International Edition, 2018)
The RGD-recognizing alpha v beta 6 integrin has only recently emerged as a major target for cancer diagnosis and therapy. Thus, the development of selective, low-molecular-weight ligands of this receptor is still in great demand. Here, a metadynamics-driven design strategy allowed us to successfully convert a helical nonapeptide into a cyclic pentapeptide (6) showing remarkable potency and alpha v beta 6 specificity. NMR and docking studies elucidated the reasons for the high affinity and selectivity of this compound, setting the ground for the rational design of new alpha v beta 6-specific small peptides or even peptidomimetics. In vivo PET imaging studies demonstrated the potential use of 6 for medical applications.

N-Methylation of isoDGR peptides: discovery of a selective alpha 5 beta 1-integrin ligand as a potent tumor imaging agent - Kapp, Tobias G.; Di Leva, Francesco Saverio; Notni, Johannes; Raeder, Andreas F. B.; Fottner, Maximilian; Reichart, Florian; Reich, Dominik; Wurzer, Alexander; Steiger, Katja; Novellino, Ettore; Marelli, Udaya Kiran; Wester, Hans-Juergen; et al. (Journal of Medicinal Chemistry, 2018)
Specific targeting of the integrin subtype alpha 5 beta 1 possesses high potential in cancer diagnosis and therapy. Through sequential N-methylation, we successfully converted the biselective alpha 5 beta 1/alpha v beta 6 peptide c(phg-isoDGR-k) into a potent peptidic RGD binding aSfil subtype selective ligand c(phg-isoDGR-(NMe)k). Nuclear magnetic resonance spectroscopy and molecular modeling clarified the molecular basis of its improved selectivity profile. To demonstrate its potential in vivo, c(phg-isoDGR-(NMe)k) was trimerized with the chelator TRAP and used as a positron-emission tomography tracer for monitoring alpha 5 beta 1 integrin expression in a M21 mouse xenograft.